Magnetic resonance imaging-derived radiomic signature predicts locoregional failure after organ preservation therapy in patients with hypopharyngeal squamous cell carcinoma. (November 2020) - Hsu, Che-Yu; Lin, Shih-Min; Ming Tsang, Ngan; Juan, Yu-Hsiang; Wang, Chun-Wei; Wang, Wei-Chung; Kuo, Sung-Hsin
Highlights: The first study to develop and validate an MRI-derived radiomic signature (RS) for the prediction of 1-year locoregional failure in HPSCC patients receiving OPT. The RS-based model (RS of 0.0326 as the cut-off value) provides a novel and convenient approach for the prediction of the 1-year clinical outcomes. The proposed RS-based model can help physicians characterize and facilitate decision-making for the clinical management of patients with locally advanced HPSCC. Abstract: Background and purpose: To develop and validate a magnetic resonance imaging (MRI)-derived radiomic signature (RS) for the prediction of 1-year locoregional failure (LRF) in patients with hypopharyngeal squamous cell carcinoma (HPSCC) who received organ preservation therapy (OPT) Material and methods: A total of 800 MRI-based features of pretreatment tumors were obtained from 116 patients with HPSCC who received OPT from two independent cohorts. The least absolute shrinkage and selection operator regression model were used to select the features used to develop the RS. Harrell's C-index and corrected C-index were used to evaluate the discriminative ability of RS. The Youden index was used to select the optimal cut-point for risk category. Results: The RS yielded 1000 times bootstrapping corrected C-index of 0.8036 and 0.78235 in the experimental (n = 82) and validation cohorts (n = 34), respectively. With respect to the subgroup of patients with stage III/IV and cT4 disease, the RS also showed good predictive performance with corrected C-indices of 0.760 and 0.754, respectively. The dichotomized risk category using an RS of 0.0326 as the cut-off value yielded a 1-year LRF predictive accuracy of 79.27%, 79.41%, 76.74%, and 71.15% in the experimental, validation, stage III/IV, and cT4a cohorts, respectively. The low-risk group was associated with a significantly better progression-free laryngectomy-free and overall survival outcome in two independent institutions, stage III/IV, and cT4a cohorts. Conclusion: The RS-based model provides a novel and convenient approach for the prediction of the 1-year LRF and survival outcome in patients with HPSCC who received OPT.